Calibration Of The Short Irradiation Facility For k0 - NAA Implementation At The IEA-R1 Reactor (Brazilian Journal of Radiation Sciences, 2021)
The short irradiation facility of the IEA-R1 nuclear research reactor at IPEN, São Paulo,  Brazil, has been used for short irradiation of samples for the purpose of determining the concentration of elements of these samples through the use of the instrumental neutron activation analysis technique. With the aim of implementing the k0-NAA method at the Neutron Activation Analysis Laboratory (LAN), the reactor parameters a and f were obtained using the bare triple method. In this method, a set of three neutron flux monitors were irradiated without Cd-cover. The efficiency curve of the gamma-ray spectrometer used was determined by measuring calibrated radioactive sources at the commonly used counting geometries. The results for the parameters a and f were respectively 0.0384±0.0016 and 35.67±0.26. This value of f shows that the neutrons in the irradiation position are well thermalized.The variation of these parameters was studied with time and the reproducibility was verified.